Does Sports Betting Affect Investment Behaviour? Evidence from Ghanaian Sports Betting Participants. - Albert Ofosu; Richard Angelous Kotey (Journal of Gambling Issues, 2020)
The study sought to assess the impact of sports betting on the investment behaviour of Ghanaians, focusing on sports betting centres within the Accra Metropolis, Ghana. The objectives of this observational study were to determine how individuals perceive the risk of sports lotteries as opposed to investment, to determine if sports lottery was viewed as an alternative to investments and savings, and to understand how participation in sports lotteries affects individuals' ability to save and invest. In adopting a survey approach, 99 sports betting participants across selected betting centres were examined using questionnaires and the data subsequently analyzed through cross-tabulations. The study found that sports betting behaviour had a complementary rather than a substitutionary effect on investment behaviour. The participants were both risk-aware and risk-averse but engaged nevertheless in betting for a chance of winning a high payoff. Thus, the findings demonstrated that sports betting participants viewed betting as a means to an end, a chance to improve their financial circumstances, rather than as a substitute for investing, and exhibited understanding of a clear distinction, with regards to behaviour, towards investing and sports betting. In return for a substantive payoff, the respondents were willing to stop sports betting, thereby indicating that the financial payoffs were the main motivation for sports betting. The findings also provided evidence that individual sports betting behaviour can be moderated by influencing one's financial circumstances. – – L'étude cherche à évaluer l'incidence des paris sportifs sur le comportement d'investissement des Ghanéens, en mettant l'accent sur les centres de paris sportifs au sein de la métropole d'Accra, au Ghana. Cette étude observationnelle vise à déterminer comment les personnes percoivent le risque lié à la loterie sportive par rapport à l'investissement, à déterminer si la loterie sportive est considérée comme une solution de rechange aux investissements et à l'épargne et à comprendre comment la participation à la loterie sportive affecte la capacité des personnes à épargner et à investir. En adoptant une approche d'enquête et à l'aide de questionnaires et de données analysées dans des tableaux croisés, on a analysé 99 participants aux paris sportifs dans les centres de paris sélectionnés. L'étude a révélé que les paris sportifs avaient un effet complémentaire plutôt qu'un effet de substitution en matière de comportement d'investissement. Les participants étaient conscients du risque et démontraient une aversion au risque, mais pariaient pour avoir la chance de remporter un gain élevé. Ainsi, les résultats ont montré que les participants aux paris sportifs considéraient ces paris comme un moyen d'atteindre une fin, une chance d'améliorer leur situation financière plutôt que comme un substitut à l'investissement. Et en ce qui concerne le comportement, ils savaient clairement faire la différence entre l'investissement et les paris sportifs. Les données ont montré qu'en échange d'un gain substantiel, les répondants étaient disposés à cesser de participer à ces paris, ce qui a permis de démontrer que les gains financiers étaient la principale motivation de ces jeux. Les résultats fournissent également des preuves étayant l'idée selon laquelle le comportement individuel lié aux paris sportifs peut être modéré en influencant la situation financière de chacun.
Keywords: E21; E22; L83; Z20; Z23; 330; Sports betting; Investment behaviour; Football gambling